SPONTANEOUS RESOLUTION OF PRIMARY HYPERPARATHYROIDISM AFTER BIOPSY- RELATED NECK HEMATOMA - Yam, Herng Pin; Tong, Chin Voon; C, Siow Ping (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND Surgical excision of the abnormal parathyroid gland remains the mainstay of treatment for primary hyperparathyroidism. We report a case of spontaneous resolution of primary hyperparathyroidism following a neck hematoma that developed post-biopsy of a thyroid nodule. CASE A 75-year-old male initially consulted with a urologist due to hematuria secondary to a left ureteric calculus. He was then found to have parathyroid-related hypercalcemia with a serum calcium of 3.10 mmol/L (2.18-2.60 mmol/L) and intact parathyroid hormone (iPTH) of 6.25 pmol/L (1.58-6.03 pmol/L). Serum total 25-hydroxyvitamin D was 67.19 nmol/L (76-250 nmol/L) for which cholecalciferol was initiated. Urinary calcium/creatinine ratio of 0.02 excluded familial hypocalciuric hypercalcemia. Imaging studies including neck ultrasound, computed tomography scan of the neck and thorax and Sestamibi parathyroid scan failed to localize the culprit lesion. He was then referred to a surgeon for exploratory parathyroidectomy. Before surgery, fine needle aspiration cytology (FNAC) of a cold thyroid nodule on the right was done which resulted in formation of a large neck hematoma. To our surprise, his calcium level started to normalise along with the resolution of the hematoma one month after the procedure. Follow-up laboratory data revealed normal calcium and PTH levels at 2.28 mmol/L and 3.87 pmol/L, respectively. Parathyroid apoplexy leading to spontaneous resolution of hyperparathyroidism is rare but has been reported. This may explain spontaneous remission of primary hyperparathyroidism in the patient probably secondary to the hematoma postbiopsy. However, because adenoma recurrence is common, he is being closely monitored. CONCLUSION Large neck hematomas leading to parathyroid apoplexy may cause spontaneous resolution of hyperparathyroidism.